Tinjauan Ulang Beban Angin SNI 1727:2020 melalui Analisis Validitas Acuan dan Implikasi Over-Design Berdasarkan Data Meteorologi Lokal - Sugema, Muhammad Rafi (Universitas Kristen Maranatha, 2026)
The Indonesian National Standard (SNI) 1727:2020 adopts a single, highly conservative basic wind speed reference, which may lead to inefficiencies in structural design. This study aims to quantify the discrepancy between the SNI reference and actual local meteorological data and to evaluate its impact on the global structural response. A quantitative comparative approach was applied by analyzing historical wind speed data from 2005 to 2024 obtained from two meteorological stations, namely Soekarno-Hatta Airport in Jakarta (WIII) and Sultan Hasanuddin Airport in Makassar (WAAA). The annual maximum wind speeds were analyzed using the Gumbel Extreme Value Distribution to estimate design wind speeds corresponding to a 700-year mean recurrence interval, and these were compared with the implicit SNI reference through a 15-story reinforced-concrete office building case study. The results revealed that the data-driven design wind speed was 42.2% lower in Jakarta and 18.5% lower in Makassar, leading to increases of more than 100% in base shear and overturning moment when the SNI reference was applied. These findings indicate that the current SNI approach is overly conservative. Therefore, developing a national wind map based on comprehensive, factual meteorological data is strongly recommended to achieve an optimal balance among safety, design efficiency, and sustainability.